A Comparative Evaluation of Sustained Release of Chlorphenamine Based on a Nanocomposite of Chitosan, Pectin and Montmorillonite. Issue 14 (11th April 2022) - Khushbu,; Vaid, Vasudha; Kaur, Kuljit; Panwar, Ankush; Devi, Anupama; Bansal, Anshul; Jindal, Rajeev
Abstract: The scenario of the current investigation is to prepare an inclusion complex (IC) of chlorphenamine (CPM) and montmorillonite (MONT) by microwave method for sustained drug delivery system and to analyze the comparison of inclusion complex with direct loading of free drug. A nanocomposite was synthesized from chitosan (CH), pectin (PC) by incorporating montmorillonite (MONT). The confirmation of inclusion complex formation and nanocomposite was characterized by FTIR, XRD, and FESEM‐EDS. Drug release study from chitosan, pectin nanocomposite containing free CPM and inclusion complex of CPM: MONT were investigated under different pH 2, 7 and 7.4 at 37 °C. The concentration of drug release from inclusion complex loaded nanocomposite was found to be 97.4 % in 22 hours. Four different kinetic models were studied to check the real mechanism involved in drug release. In all cases, the best fitted kinetic model for CPM release from the inclusion complex loaded nanocomposite was Peppas‐Sahlin and Korsmeyer Peppas, implying that diffusion and relaxation phenomena were responsible for the drug release. Diffusion phenomena have more contribution than relaxation is confirmed by the Peppas‐Sahlin equation. Montmorillonite is responsible for the sustained drug release because of host‐guest interactions. Montmorillonite has a layered structure that allows it to intercalate the drug molecule into its cavity, resulting in sustained chlorphenamine release. Abstract : Inclusion complexes of montmorillonite and chlorphenamine were prepared by microwave method for sustained and controlled drug delivery system. Incorporation of montmorillonite greatly enhanced the swelling capacity of the Chitosan and pectin hydrogel. Nanocomposite has high loading and sustained release of CPM as compare to Chitosan and pectin hydrogel. Comparison of drug release kinetics of free CPM and ICs of CPM: MONT from the nanocomposite at different pH were analyzed to know about the mechanism of drug release.